Komunikasi Keluarga Penyintas Covid-19 di Pedesaan: (Studi Kasus Banyumas dan Cilacap) - Agus Ganjar Runtiko; Edi Santoso (Universitas Serang Raya, 2021)
The Covid-19 pandemic that has lasted for more than a year has changed many things. One thing that has changed is family communication, especially one whose members have been confirmed positive for Covid-19. This study aims to determine: 1) the communication patterns of the families of covid-19 survivors; 2) the supporting and inhibiting factors in healing psychological trauma due to Covid-19; and 3) the communication patterns of the survivors before, during, and after recovering from Covid-19. The research method used is a case study conducted in Sawitan Village, Banyumas Regency, and Rikmayung Village, Cilacap Regency. The study results show that: 1) family members are the prominent supporters of communication during survivors experiencing symptoms of Covid-19, and during the initial recovery period and socializing with the community; 2) the supporting factor for healing psychological trauma is family communication with a positive tone and good communication with neighbours and the environment, while the inhibiting factor is communication avoidance, and 3) Covid-19 survivors tend to communicate more empathy with other sufferers and are more careful in carrying out health protocols.